Simple proof of the risk bound for denoising by exponential weights for asymmetric noise distributions - Dalalyan, A. S. (Հայաստանի ԳԱԱ)
In this note, we consider the problem of aggregation of estimators in order to denoise a signal. The main contribution is a short proof of the fact that the exponentially weighted aggregate satisfies a sharp oracle inequality. While this result was already known for a wide class of symmetric noise distributions, the extension to asymmetric distributions presented in this note is new.
Keywords: Mathematics